A Great and Terrible Beauty - Bray, Libba (New York : Delacorte Press, 2003)
After the suspicious death of her mother in 1895, sixteen-year-old Gemma returns to England, after many years in India, to attend a finishing school where she becomes aware of her magical powers and ability to see into the spirit world.
Keywords: Magic -- Fiction; Supernatural -- Fiction; Boarding schools -- Fiction; Schools -- Fiction; England -- Social life and customs -- 19th century -- Fiction